The Resonant Table: Drinking-Songs in the Traditional Community Gatherings - Ivanauskaitė-Šeibutienė, Vita (Tautosakos darbai, 2015)
The article focuses on the traditional Lithuanian drinking-songs that used to particularly flourish and be amply recorded by the folklore collectors in the 19th century and the first half of the 20th century. The prevailing folkloric motives in these songs include the making of the drinks (most frequently, the beer), inviting of the guests and an insistent encouraging them to help themselves, to drink “to the bottom”, praising of the neighbors and relatives, etc. Direct connections of these songs to the verbal formula of the table etiquette, used to wish others good health and prosperity, as well as to the traditional entertainment customs in general are examined. The traditional Lithuanian feasts did not comprise any sufficiently developed toasting tradition that used to play an outstanding role in some other national cultures. Therefore, it is justified to assume that its place was taken instead by the drinkingsongs. A significant number of the drinking-songs used to make an integral part of the important community festivals, primarily – of the weddings. Inevitable decline of the festive rituals resulted in related songs finding their way into various community gatherings as mere pieces of entertainment. Such shift in context and purpose of these songs may be attributed to the broader changes taking place in the rituals of social solidarity: from the ancient offerings of drink to the contemporary toasting of each other by the members of the festive gathering. The drinking-songs stand out among other traditional Lithuanian songs in terms of their folkloric imagery, characterized by its peculiar ritual connections, unique hyperboles and specific kind of laughter, and rooted deeply in the traditional festive culture and dynamics of the social communication.